2007
DOI: 10.1111/j.1651-2227.2006.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Working mothers breastfeed babies more than housewives

Abstract: The rates of any breastfeeding and exclusive breastfeeding during the first year of life were fairly satisfactory. Programs to support breastfeeding are necessary and should encourage women to feel positive to breastfeed, focusing particularly on non-working mothers, mothers with a maternity entitlement less than 6 months and mothers who lack previous breastfeeding experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
2
23
0
8
Order By: Relevance
“…A experiência prévia com a amamentação tem sido associada com uma duração maior da amamentação e do aleita- mento materno exclusivo 29 . Este achado reforça a importância de um apoio maior às mulheres que ainda não amamentaram ou que amamentaram por pouco tempo seus filhos anteriormente.…”
Section: Discussionunclassified
“…A experiência prévia com a amamentação tem sido associada com uma duração maior da amamentação e do aleita- mento materno exclusivo 29 . Este achado reforça a importância de um apoio maior às mulheres que ainda não amamentaram ou que amamentaram por pouco tempo seus filhos anteriormente.…”
Section: Discussionunclassified
“…In contrast to other study done by Bakoula et al, the study found that working mothers had more intention to breastfeed and breastfeed longer than housewives. The lengthier the mothers entitled to maternity leave, the longer duration of breastfeeding (Bakoula et al, 2007). The dissimilarity can be explained by housewives were more likely intending to breastfeed due to economic restrain and they had extra bonding time with their babies as compared to working mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The first questionnaire was completed by mothers at recruitment in the hospital antenatal clinic, with a follow-up interviewer-administered questionnaire at 6 weeks and 6 months postpartum, either in the hospital clinic, in the mothers' home or via telephone. Questions addressed breast-feeding initiation and duration (45) , maternal perceptions and attitudes (46) , ethnic considerations (47) , factors related to the partner (10) and mother's employment status (48,49) . All three questionnaires were pre-tested on three separate pilot groups.…”
Section: Data Collectionmentioning
confidence: 99%